Psycholinguistic approach to the analysis of manipulative and indirect hate speech in media - Krylova-Grek, Yuliya (Lesya Ukrainka Eastern European National University, 2022)
The present study takes a psycholinguistic approach to the analysis of Russian media texts published between 1 December 2020 to 31 May 2021. I aimed to provide a scientific basis for the existence of manipulative and indirect hate speech using an interdisciplinary methodology comprising linguistic, psycholinguistic, and other analytical methods such as fact-checking and logical analysis. This facilitated the identification of techniques employed by the authors of the respective texts. In the article, I describe how I use the methodology to analyse media texts. I discovered that three basic types of hate speech were used to influence the audience’s consciousness: (1) direct hate speech; (2) indirect (hidden) hate speech; and (3) manipulative hate speech. The first and second types were the most common. This may be explained by the fact that direct hate speech is condemned by international organisations and its use may be a reason for lawsuits against media outlets and their further penalisation. Texts with evidence of the second and third types of hate speech aimed to create a negative attitude toward a particular nationality, race, citizen, and so on. I consider such behaviour to be an early manifestation of widespread discrimination and other forms of intolerance, including possible violence and genocide. The present study was carried out in collaboration with a Crimean human rights group. The author was invited to participate as an expert in the field of psycholinguistic textual analysis. The research was prepared and completed at the beginning of February 2022, on the eve of the invasion of Ukraine. We have gathered evidence of indirect and manipulative hate speech that dehumanised, demonised, and marginalised Ukrainian citizens. This has led to violence against the civilian population and high numbers of casualties. The aforementioned methodology will continue to be used in the analysis of current media content.
Keywords: media text; psycholinguistic analysis; Ukraine; war; hate speech